Intratumoral heterogeneity in EGFR mutant NSCLC results in divergent resistance mechanisms in response to EGFR tyrosine kinase inhibition - Soucheray, Margaret (Cancer Res, 2015)
Non-small cell lung cancers (NSCLC) that have developed resistance to epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs), including gefitinib and erlotinib, are clinically linked to an epithelial-to-mesenchymal transition (EMT) phenotype. Here we examined whether modulating EMT maintains the responsiveness of EGFR-mutated NSCLCs to EGFR TKI therapy. Using human NSCLC cell lines harboring mutated-EGFR and a transgenic mouse model of lung cancer driven by mutant EGFR (EGFR-Del19-T790M), we demonstrate that EGFR inhibition induces TGFβ secretion followed by SMAD pathway activation, an event that promotes EMT. Chronic exposure of EGFR-mutated NSCLC cells to TGFβ was sufficient to induce EMT and resistance to EGFR TKI treatment. Furthermore, NSCLC HCC4006 cells with acquired resistance to gefitinib were characterized by a mesenchymal phenotype and displayed a higher prevalence of the EGFR T790M mutated allele. Notably, combined inhibition of EGFR and the TGFβ receptor in HCC4006 cells prevented EMT, but was not sufficient to prevent acquired gefitinib resistance because of an increased emergence of the EGFR T790M allele compared to cells treated with gefitinib alone. Conversely, another independent NSCLC cell line, PC9, reproducibly develops EGFR T790M mutations as the primary mechanism underlying EGFR TKI resistance, even though the prevalence of the mutant allele is lower than that in HCC4006 cells. Thus, our findings underscore heterogeneity within NSCLC cells lines harboring EGFR kinase domain mutations that give rise to divergent resistance mechanisms in response to treatment and anticipate the complexity of EMT suppression as a therapeutic strategy.